In Vitro Anti-Biofilm Activity of Nutmeg (Myristica fragrans) Leaf Infusion Extract - Wijayanti, Faulia Triana; Nugroho, Yusuf Eko; Pangesti, Ira (poltekkes kemenkes pontianak, 2025)
Pseudomonas aeruginosa is an opportunistic Gram-negative bacterium commonly associated with severe infections, particularly in immunocompromised individuals. One of its major virulence factors is biofilm formation, which contributes to increased antimicrobial resistance. This study aimed to evaluate the inhibitory activity of nutmeg (Myristica fragrans) leaf infusion extract against P. aeruginosa biofilm formation in vitro. The experiment was conducted using a 96-well microtiter plate assay, and biofilm intensity was quantified at 595 nm following crystal violet staining. The results demonstrated that the nutmeg leaf infusion extract significantly inhibited biofilm formation, with varying levels of effectiveness depending on incubation time. These findings indicate the potential of nutmeg leaf infusion extract as an antibiofilm agent against P. aeruginosa.